Cognitive enhancement and neuroprotection by catechin-rich oil palm leaf extract supplement - Mohamed, Suhaila; Tan, Lee Ming; Md. Jaffri, Juliana (Elsevier Inc., 2013)
BACKGROUND: Catechin-rich oil palm (Elaeis guineensis) leaf extract (OPLE) has good cardiovascular and phytoestrogenic properties. The OPLE (0.5 g day(-1) ) was supplemented to young, healthy, adult human volunteers, and their cognitive learning abilities were compared to placebo-controlled groups (N = 15). Their short-term memories, spatial visualisations, processing speeds, and language skills, were assessed over 2 months by cognitive tests computer programs. RESULTS: Relative to the controls, volunteers taking OPLE had improved (P < 0.05) short-term memory, after 1 month of intervention which became highly significant (P < 0.005) after 2 months. The spatial visualisation ability and processing speed improved (P < 0.05) after 2 months consumption. The dietary OPLE showed neuroprotection in nitric oxide-deficient rats. The mechanisms involved systemic and cellular modulations that eventually enhance neuron survival. The longer the duration of OPLE consumption, the more significant was the enhancement, as shown for short-term memory. CONCLUSION: This is the first report on the cognitive-enhancing effects of dietary OPLE in humans. The computer-assisted cognitive tests were simple, low in cost, errors and man hours, and hence are better than conventional cognitive test methods. In rats, the equivalent OPLE dose showed brain antioxidant enzymes modulating properties and neuroprotection under nitric oxide deficiency, with possibly neurogenesis in normal rats. This supported the effects in humans. Copyright Â© 2012 Society of Chemical Industry.